Phytochemistry and pharmacological potential of aloscasia macrorrhiza: A comprehensive review - Chakraborty, Amitesh; Giri, Santanu; Shah, Aditya Dev; Adhikari, Tushar (Journal of Applied Pharmaceutical Research, 2024)
Background: Aloscasia macrorrhiza, commonly known as Giant Taro, is a species rich in phytochemicals with diverse pharmacological properties. Phytochemical analysis shows different bioactive compounds like alkaloids, flavonoids, terpenoids, phenolics, and saponins in different components of the plant body, including leaves, stems, and roots. Alocasin, a class of alkaloids, is most prominent in this plant. These substances are likely responsible for different biological activities, as Aloscasia macrorrhiza shows. Aim: This review unveils the phytochemical composition and pharmacological activities of various parts of Aloscasia macrorrhiza. Method: Multiple Literature, including research and review papers, were searched for based on their title, abstracts, and keywords. Keywords like ‘Aloscasia macrorrhiza,’ ‘Phytochemistry,’ ‘Traditional uses,’ and ‘Ethnomedicinal uses’ were used to collect information. Abstracts of articles with relevant titles were screened, and the full text was considered. Only articles published from 2018 to 2024 were considered. Based on their classes and mechanistic actions, this review consolidated these phytoconstituents. Results: These phytoconstituents exhibit a wide array of therapeutic activities, including anti-inflammatory (due to tannins and polyphenols), antimicrobial (due to terpenes and lectins), antioxidant (due to polyphenols), anticancer (due to flavonoids), anti-diabetic (due to flavonoids) effects. Conclusion: This review provides insights to the therapeutic potential of Aloscasia macrorrhiza and hence forms a bridge of understanding between the traditional uses and the modern Pharmacology studies. In the future, further clarification and detailed mechanistic insight can be done. Aloscasia macrorrhiza may have potential therapeutic applications and is subject to further investigation.